Laparoscopic Cholecystectomy at Shree Birendra Hospital - Malla, S; Rawal, SB; Giri, NK (Medical Journal of Shree Birendra Hospital, 2012)
Introduction: Since its introduction in Shree Birendra Hospital, laparoscopic cholecystectomy has gradually replaced its open counterpart. Along with its superior results, surgeons had to deal with the difficult challenges of managing bile duct injuries. Methods: A prospective study of all laparoscopic cholecystectomies performed in the General surgical unit of Shree Birendra Hospital from January 2003 to December 2010 was carried out from case records in a separate register kept for laparoscopic surgeries. Results: Out of the total number of 786 patients who underwent laparoscopic cholecystectomy during the study period, 21 (2.67%) required conversion to open procedure with the most common indication being unclear anatomy at Calot’s triangle. There were 14 major post operative complications (1.78%) with bile duct injuries occurring in 7 patients (0.89%). Among these injuries, 3 injuries were recognized during the primary operation. Laparotomy with t tube placement for 6 weeks was the mode of treatment in 2 patients with Strasberg type D injuries detected post operatively. Delayed repair after 3 months were carried out in 2 injuries- one hepaticojejunostomy (Type E2) and the other required anastamosis to the left hepatic duct (Type E3). In follow up, these patients have remained aniciteric and comfortable so far. Conclusion: Bile duct injuries continue to remain a major morbidity factor in laparoscopic cholecystectomy and its management a challenge to the surgeon. Though repair in a specialized hepatobiliary center is recommended, in the absence of such center in our country, it is being done in SBH with good results. DOI: http://dx.doi.org/10.3126/mjsbh.v10i1.6444 Medical Journal of Shree Birendra Hospital Jan-June 2011 10(1) 15-19